EXPERIENCE OF LITHOGEOCHEMICAL EXPLORATION OF GOLD MINERALIZATION: (on example of Pkhrut uranium ore) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
According to the results of lithogeochemical soil sampling within the Pkhrut uranium ore field besides uranium anomalies secondary dispersion halos of gold and associated indicator-elements were revealed. Application for the assessment of these halos, three dimensional geochemical modelling of some known (standard) deposits has been used and it permitted to select two promising anomalies of gold.
Keywords: lithogeochemical soil sampling; Pkhrut uranium ore field; indicator-elements